2021
DOI: 10.3390/ph14070607
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2/ARE Activators Improve Memory in Aged Mice via Maintaining of Mitochondrial Quality Control of Brain and the Modulation of Gut Microbiome

Abstract: Aging is one of the most serious factors for central nervous dysfunctions, which lead to cognitive impairment. New highly effective drugs are required to slow the development of cognitive dysfunction. This research studied the effect of dimethyl fumarate (DMF), methylene blue (MB), and resveratrol (RSV) on the cognitive functions of 15-month-old mice and their relationship to the maintenance of mitochondrial quality control in the brain and the bacterial composition of the gut microbiome. We have shown that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 89 publications
1
33
0
Order By: Relevance
“…Akkermansia muciniphila mitigates intestinal barrier dysfunction, reduces the deposition of Aβ plaques in the brain, promotes cognitive function, and delays pathological changes in the brain ( Ou et al, 2020 ; Higarza et al, 2021 ). Negativibacillus has a positive correlation with cognition ( Sadovnikova et al, 2021 ). Clostridium can synthesize 3-indolepropionic acid, a strong antioxidant that can scavenge free radicals produced by D-gal, thus protecting the brain from oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia muciniphila mitigates intestinal barrier dysfunction, reduces the deposition of Aβ plaques in the brain, promotes cognitive function, and delays pathological changes in the brain ( Ou et al, 2020 ; Higarza et al, 2021 ). Negativibacillus has a positive correlation with cognition ( Sadovnikova et al, 2021 ). Clostridium can synthesize 3-indolepropionic acid, a strong antioxidant that can scavenge free radicals produced by D-gal, thus protecting the brain from oxidative damage.…”
Section: Discussionmentioning
confidence: 99%
“…MB improved cognitive function in 15-month-old mice in Morris water maze. In particular, MB increased the values of short-term memory and caused a decrease in the distance that mice spent searching for the platform during the learning phase for LTM estimation [ 27 ]. The randomized, double-blinded, placebo-controlled clinical trial showed that MB administration increased response in the bilateral insular cortex during a psychomotor vigilance task and was also associated with a 7% increase in correct responses during memory retrieval [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can transfer electrons in the electron transport chain from NADH and FADH2 directly to cytochrome C, bypassing complexes I–III; thereby improving mitochondrial function with affected complexes [ 25 ]. It is known that a low concentration can modulate the composition of the gut microbiome [ 26 , 27 ]. Correlation analysis showed that MB-induced changes in the bacterial composition of the gut microbiome correlate with the improved cognitive phenotype of mice.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that TBI can enhance the expression of NLRP3 [ 192 , 196 ] and caveolin-1 [ 193 ], and impede Nrf2 signalling [ 192 , 197 ], and these changes are also displayed in gut diseases [ 198 , 199 , 200 ]. Among them, NLRP3 and Nrf2 are the potential mediators in BGA dysfunction [ 198 , 201 , 202 ]. Moreover, there is clear evidence that m 6 A mediates gene expression and the signal pathway [ 191 , 203 , 204 ].…”
Section: The Role Of M 6 a Rna Modification In Tbi...mentioning
confidence: 99%
“…Furthermore, the expression of NLRP3 inflammasome proteins can be induced by oxidative stress through increasing the expression of key proteins of the Nrf2/HO-1 pathway following TBI [ 192 ]. Additionally, Nrf2 activators have an influence on mitochondrial quality control and are correlated with a positive change in BGA [ 202 ]. Hence, TBI-induced METLL3 downregulation may induce oxidative stress and neuroinflammation via the METLL3/miR-873-5p/Keap1/Nrf2 signalling pathway, consequently leading to BGA dysfunction.…”
Section: The Role Of M 6 a Rna Modification In Tbi...mentioning
confidence: 99%